Comparison of Science Process Skills of Students at SMAN 16 Samarinda Based on Gender - Kevin Jeremia Hutauruk; Farah Erika; Sukemi Sukemi; Muflihah Muflihah; Maasje Catherine Watulingas (Jambura Journal of Educational Chemistry, 2026)
Science process skills (SPS) are essential competencies in chemistry learning that support development of scientific thinking and evidence-based problem solving. This study aimed to analyze differences in students' SPS based on gender in chemistry learning at a public senior high schools in Samarinda. The study used a retrospective comparative quantitative approach. The SPS data were collected by using documentation technique involving 65 SPS of eleventh grade students (31 males and 34 females) who programmed chemistry subject. SPS data were analyzed descriptively and inferentially using the Mann-Whitney U test (α = 0.05). The results showed that there was no significant difference in overall SPS between male and female students (p = 0.333) and in most indicators (p > 0.05), except for the observation indicator (p = 0.004), with female students having a slightly higher descriptive mean. These findings confirm that mastery of SPS is more influenced by the quality of the learning process than by gender factors, thus contributing empirically to the application of inclusive science learning oriented towards scientific activities.